Challenges of Students In Learning The Islamic Yellow Book at Dayah Raudhatul Qur'an Darussalam, Aceh Besar, Indonesia - Fahmi Makraja; Ulil Azmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
This research discusses the challenges of Dayah Raudhatul Qur'an Darussalam students in learning the yellow book. Dayah Raudhatul Qur'an Darussalam is one of the traditional dayahs in Aceh Besar district that still maintains the concept and learning model of classical